A Triptych on Schleiermacher's On Religion - Borgman, Erik (Literature and theology, 2007)
The following three texts form a triptych in the classic meaning this term has in late medieval painting. They are independent panels with their own themes, arguments and disciplinary background (literary theory, philosophy and theology); and still they ‘live’ from constant reference to and dependance on one another. They were first presented at the International Society for Religion, Literature and Culture's conference ‘Sacred Space’ in Stirling, Scotland, October 2006, and later reworked thoroughly.There common focus is a series of new readings of Friedrich Schleiermacher's (1768–1834) famous On Religion: Speeches to its Cultured Despisers (1799). In the first article, Bart Philipsen explores the intellectual context of this book, especially Schleiermacher's relation to the Early Romanticists, and focuses on the hermeneutical, rhetorical and poetical questions and strategies through which Schleiermacher's performative concept of religion is developed. In the second article, Laurens ten Kate treats a key concept in Schleiermacher's account of the meaning of religion in modern culture, that of intuition; he investigates the relation between intuition and performativity, and analyses the influence of Kant's philosophy at this point. In the third article, Erik Borgman studies and evaluates the central notion of melancholy in Schleiermacher's views on religion, and, comparing these with the thought of Rudolf Otto and Edward Schillebeekx, he pleads for a new understanding of the way Schleiermacher should be called a modern thinker.